(untitled) (TEST Ticontre. Theory Text Translation, 2026)
This contribution investigates the reception of Goethe in Alfred Döblin’s essays and narrative work. Starting with an analysis of some of the Berlin writer’s autobiographical writings and the essays Goethe und Dostojewski and Wissen und Verändern!, the complex evolution of his relationship with Weimar Classicism is outlined and the influence of Goethe’s morphology in Döblin’s thought is highlighted. On the basis of the study of poetological writings, the points of contact between the classical concept of the autonomy of the parts and the modern epic conceptualised by Döblin are then shown. Finally, through the analysis of the structure and intertextual elements in the exile novel Amazonas, we focus on Döbllin’s reading of the Faustian theme.